THE EFFECTIVENESS OF SPEED READING AS TECHNIQUE IN TEACHING READING COMPREHENSION OF TENTH GRADE AT MA. SUNAN CENDANA MADURA - Lailatul Qomariah; Rahmat Efendi (FKDP (Forum Komunikasi Dosen Peneliti), 2019)
The objective of the research is to know the students’ achievement using speed reading technique in teaching reading comprehension. The research is carried out at MA Sunan Cendana Madura. The method non-randomized experimental study and the number of experimental class is 22 and 23 for control class. The researcher uses ANCOVA (Analysis of Covariance. The result shows that the pretest average score of each group is different. The pretest score of experimental group is 61.36 and control group is 44.35. Then, the post-test average score of the experimental group is 87,27 and the control group is 56,52. It is found that the value of F is 33,18. It is found that F critical with df 43 at 0.01 level of significance to 7,08. It means that F value is higher than F critical score. The result of data analysis above shows that: (1) speed reading technique is more effective than the conventional technique on reading comprehension.